2021
DOI: 10.1111/dth.14882
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase 2 and vascular endothelial growth factor–potential targets to manage lepra reactions: A case‐control study

Abstract: Reactions in leprosy have an immune mediated pathogenesis. While type 1 reactions are delayed hypersensitivity phenomenon, type 2 reactions are immune complex mediated. Key molecules which mediate the immune insult in lepra reactions require evaluation in order to tailor their therapy and prevent disability. The objective of the study was to evaluate expressions of Cyclooxygenase 2 and Vascular Endothelial Growth Factor in skin biopsies from leprosy patients and correlate their expression with presence of eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…22 But our review found that one study reveals VEGF is overexpressed in T1R 13 meanwhile another study found nondifference of VEGF in T1R compared to non-T1R. 15 Therefore, the role of COX-2 in T1R through this VEGF pathway is controversial.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…22 But our review found that one study reveals VEGF is overexpressed in T1R 13 meanwhile another study found nondifference of VEGF in T1R compared to non-T1R. 15 Therefore, the role of COX-2 in T1R through this VEGF pathway is controversial.…”
Section: Discussionmentioning
confidence: 97%
“…Based on their treatment status, patients who were on medication had a higher risk of COX-2 expression than non-on-treatment patients (191.50 ± 56.76 vs 141.98 ± 78.85). 15 Genetic studies have also shown that the PTGS2 gene (central gene in the Arachnoid Acid Pathway) encoding COX-2 is up-regulated in T1R patients. In addition, the TNFAIP6 gene encodes TNFstimulated gene 6 (TSG6), whose function as an inducer of COX-2 expression in macrophages is also upregulated in earlyonset T1R.…”
Section: Original Articlementioning
confidence: 99%